Peran Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Kalimantan Tengah dalam Penyelenggaraan Bantuan Hukum untuk Masyarakat Miskin - Reza Ardianto; Jalaludin Muhammad Akbar; Risky Al Ahli; Desi Rahmawati; Akbar Nur Azmi; Zainal Maarif (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The right to legal aid is a fundamental entitlement of every citizen, aimed at ensuring access to justice, safeguarding human rights, and providing equal opportunities for legal assistance, particularly for those who face economic challenges. In democratic legal systems, legal aid serves as a crucial mechanism to uphold equality before the law and prevent injustices caused by unequal access to legal resources. The state is responsible for guaranteeing that legal aid is available to its citizens, whether through the provision of qualified lawyers or accessible legal aid institutions, to support individuals throughout legal proceedings, both in criminal and civil cases. Legal aid extends beyond the economically disadvantaged, also covering vulnerable groups such as women, children, persons with disabilities, and other marginalized minorities who are often excluded from the judicial process. In this sense, legal aid plays an essential role in ensuring that every citizen’s rights are protected and that legal proceedings are fair and just. Furthermore, in order to ensure that everyone, regardless of social or economic background, receives equitable and unbiased treatment in legal proceedings, the right to legal assistance is essential to bolstering the rule of law.